Association Analysis Revealed That TaPYL4 Genes Are Linked to Plant Growth Related Traits in Multiple Environment - Xue, Yinghong; Wang, Jingyi; Mao, Xinguo; Li, Chaonan; Li, Long; Yang, Xi; Hao, Chenyang; Chang, Xiaoping; Li, Runzhi; Jing, Ruilian (Frontiers in Plant Science, 2021)
Abscisic acid (ABA), one of phytohormones, plays an important regulatory role in plant growth and development. ABA receptor PYL4 (pyrabactin resistance 1-like 4) was previously detected to be involved in plant response to a variety of stresses. TaPYL4 overexpression could enhance wheat (Triticum aestivum) drought resistance. In order to further investigate TaPYL4’s role in regulating development of other major agronomic traits in wheat, genes of TaPYL4-2A, TaPYL4-2B, and TaPYL4-2D were cloned from wheat, respectively. Polymorphism analysis on TaPYL4 sequences revealed that encoding regions of the three genes were highly conserved, without any SNP (single nucleotide polymorphism) presence. However, nine SNPs and four SNPs were identified in the promoter regions of TaPYL4-2A and TaPYL4-2B, respectively. Functional molecular markers were developed based on these polymorphisms, which were then used to scan a natural population of 323 common wheat accessions for correlation analysis between genotype and the target phenotypic traits. Both TaPYL4-2A and TaPYL4-2B markers were significantly correlated with plant growth-related traits under multiple environments (well-watered, drought and heat stress treatments). The additive effects of TaPYL4-2A and TaPYL4-2B were verified by the combinational haplotype (Hap-AB1∼Hap-AB4) effects determined from field data. Cis-acting elements were analyzed in the promoters of TaPYL4-2A and TaPYL4-2B, showing that a TGA-element bound by ARFs (auxin response factors) existed only in Hap-2A-1 of TaPYL4-2A. Gene expression assays indicated that TaPYL4-2A was constitutively expressed in various tissues, with higher expression in Hap-2A-1 genotypes than in Hap-2A-2 materials. Notably, TaARF4 could act as TaPYL4-2A transcription activator in Hap-2A-1 materials, but not in Hap-2A-2 genotypes. Analysis of geographic distribution and temporal frequency of haplotypes indicated that Hap-AB1 was positively selected in wheat breeding in China. Therefore, TaPYL4-2A and TaPYL4-2B could be a valuable target gene in wheat genetic improvement to develop the ideal plant architecture.